2012
DOI: 10.1007/s11764-012-0227-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of reproductive health counseling at the time of cancer diagnosis: a qualitative study of female California cancer survivors

Abstract: Many women may not receive adequate information about RHRs or FP at the time of cancer diagnosis. Advancements in reproductive technology and emerging organizations that cover financial costs of FP have dramatically changed what options women have to preserve their fertility. Routine and thoughtful RHR and FP counseling, as well as collaborative cancer care will help ensure that women diagnosed with cancer are provided with the services and information they need to make an informed choice about their reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 41 publications
4
99
2
4
Order By: Relevance
“…Moreover, concerns about infertility are not limited to patients who are young and childless or/and have a partner [41]. It has been reported that up to 70-75% of young cancer survivors would like to have a child [39,42] with up to 29% of women refusing life saving treatment because of fear to become infertile [42], including a case reports where refused therapy lead to foetal and maternal death [43]. However, significantly lower numbers actually proceed with fertility preservation procedures ( Table 2).…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, concerns about infertility are not limited to patients who are young and childless or/and have a partner [41]. It has been reported that up to 70-75% of young cancer survivors would like to have a child [39,42] with up to 29% of women refusing life saving treatment because of fear to become infertile [42], including a case reports where refused therapy lead to foetal and maternal death [43]. However, significantly lower numbers actually proceed with fertility preservation procedures ( Table 2).…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
“…However, even women with positive attitudes about having children after cancer have fears that possible pregnancy would increase chances for cancer recurrence or transmitting the cancer risk to the future child [47,48]. On the other hand patients who already have children might focus more on survival than fertility preservation [40,42] and as a result might be less likely to be offered fertility preservation consultation [46,49]. Therefore, discussing cancer treatment implications on fertility and possible fertility preservation options as well as providing patients with decisional support would significantly help to improve cancer care and benefit the patients in any country.…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
“…Providers have cited a discomfort in their own knowledge of fertility information and studies have found an association between physician discomfort and fertility discussion practice. 19,20,22,24,39,55,[58][59][60] Providers report a concern about causing anxiety for the patient and a pressure to initiate cancer treatment immediately, despite research showing otherwise, that counseling patients increases compliance and decreases their anxiety. 24,39 In fact, simply providing the patient with written information about fertility threats may be sufficient enough to initiate a fertility discussion and proper referral to a fertility specialist.…”
Section: Practice Guidance For Fertility Preservationmentioning
confidence: 99%
“…The fertility concerns of aya cancer patients while on therapy and after therapy discontinuation have been documented to be one of the major causes for their anxiety [7][8][9][10][11] . Chemotherapy and radiotherapy can be gonadotoxic, resulting in impaired fertility [12][13][14] .…”
Section: Medical Issuesmentioning
confidence: 99%
“…Impaired fertility requires discussion and consideration for fertility preservation referral, by the aya health care professionals, at the time of the patient's diagnosis, before the onset of therapy, and again later in the post-therapy period 14 . Reluctance on the part of health care professionals to discuss impaired fertility in ayas is well documented 7,8,11,12 . The American Society of Clinical Oncology published specific practice guidelines in 2006 and updated them in 2013 14 .…”
Section: Medical Issuesmentioning
confidence: 99%